Hypnotic Effect and GC-MS Analysis of Seeds Extracts From Algerian Nopal (Opuntia ficus-indica L.) - Farah Kenza BENATTIA (PhytoChem & BioSub Journal, 2017)
Context: Sleep disorders are a frequent symptom that requires prior to any prescription medication, an etiological check to eliminate any organic or psychiatric pathology that is under other treatments and that could worsen under hypnotics.The phytochemical study of Nopal affirm to be an excellent source of natural oligoelements which may improve human health and nutrition Aims: The objective of this work is to extract and analyze the lipid fraction of prickly pear seeds (Opuntia ficus–indica. L), and to determine their hypnotic activity in order to achieve a primary pharmacological screening contained in these extracts (aqueous, hydro-ethanol). Methods: GC-MS analysis of seed oil extracted by soxhlet method, and the pharmacology experiment was performed on white mice from a Swiss race Balb/cby calculating the sleep time. Results: The oil of seeds is rich in fatty-acids poly-unsaturates, Main fatty acids identified were linoleic (C18:2), oleic (C18:1), and palmitic (C16:0), palmitoleic (C16:1) acids with respective contents 81.25%, 3.70%, and 15.03%. The extract hydro-ethanolic at the 500mg / kg dose has a moderate hypnotic effect Conclusion: This study proves that the food quality of prickly pear seeds is very important and its natural source of edible oil containing of the essential fatty-acids, and can be a base for a promising work to highlight the bioactive moleculeswithhypnotic effects, myorelaxant and tranquillizing.